Preoperative percutaneous needle indigo carmine and lipiodol mixture marking in lung segmentectomy. (30th August 2022) - Matsui, Takuya; Takahashi, Yusuke; Nakada, Takeo; Sakakura, Noriaki; Hasegawa, Takaaki; Sato, Yozo; Inaba, Yoshitaka; Haneda, Hiroshi; Okuda, Katsuhiro; Nakanishi, Ryoichi; Kuroda, Hiroaki
Abstract: OBJECTIVES: For successful nodule localization and appropriate surgical margin distances in pulmonary segmentectomy for patients with lung malignancies, the effectiveness and feasibility of preoperative marking using an indigo carmine and lipiodol mixture remain unclear. METHODS: Patients who underwent thoracoscopic pulmonary segmentectomy with (marking group, n = 69) and without (non-marking group, n = 265) preoperative marking at our institution from January 2013 to March 2020 were retrospectively reviewed and compared in terms of surgical outcomes. All markings were performed using a fine needle to percutaneously inject an indigo carmine and lipiodol mixture under the guidance of computed tomography fluoroscopy. RESULTS: Successful localization was achieved in 66 (96%) patients, of whom 62 (94%) underwent dye pigmentation and 4 (6%) underwent intraoperative fluoroscopy. On images, the marking group showed a significantly longer distance between the lung surface and tumour [mm, 9 (1–17) vs 0 (0–10); P < 0.01] and smaller maximum tumour size [mm, 16 (11–21) vs 17 (13–23); P = 0.03] and consolidation tumour ratio [0.4 (0.3–1) vs 0.8 (0.4–1); P < 0.01] than the non-marking group. Both groups had comparable operative outcomes, perioperative complications, pulmonary function changes and surgical margin distances [mm, 20 (15–21) vs 20 (15–20); P = 0.96] without any local recurrence on the surgical margin. Propensity score-matching analysis also showed similar findings for both groups. CONCLUSIONS: Thoracoscopic pulmonary segmentectomy with preoperative marking using an indigo carmine and lipiodol mixture may be an acceptable therapeutic option for small malignancies located in deep lung parenchyma. Abstract : Recent advancements in radiological diagnostic and surgical techniques have gradually facilitated the widespread use of pulmonary segmentectomy for lung malignancies [1, 2].